Synthesis of Ester from Waste Cooking Oil (WCO) and Pentaerythritol via Dean-Stark Distillation for Potential Use as Biolubricant - Juliati Br Tarigan; Ebenezer Primsa Ginsu; Cut Fatimah Zuhra (Talenta Publisher, 2025)
Waste cooking oil (WCO) is a group of oils or fats that have been used for cooking or frying repeatedly and are no longer suitable for use. Repeated heating of cooking oil will cause the formation of trans fatty acids that trigger coronary heart disease (CHD). This study aims to synthesize esters as biolubricant candidates from WCO. WCO was purified using 0.05% (v/v) of H3PO4 and 2% (w/v) of bleaching earth, then saponified with ethanolic NaOH and hydrolyzed with 25% H₂SO₄. The fatty acids obtained were then esterified with pentaerythritol using a dean-stark distillation apparatus with 2% H2SO4 catalyst and toluene solvent at a temperature of 170-180°C for 6 hours. The results of the acid number analysis showed an ester conversion of 83.08%. Furthermore, the FT-IR spectra showed the presence of C=O (1730 cm⁻¹) and C–O–C (1178 cm⁻¹) groups, indicating the formation of esters. These results indicate that esters from used cooking oil have the potential to be environmentally friendly biolubricants.